Creative Economic Development Strategies and Contributions to the Economic Development of Kediri City 2016-2019 - Ellis Susmawati; Sugiono; Subagyo (CV. AFDIFAL MAJU BERKAH, 2022)
This research was based on the background that in 2019 the contribution of the creative economy to the national GDP (Gross Domestic Product) was 5.10 percent or Rp. 95 trillion, employment was 19.01 million individual and export value was 22.07 Billion USD. In the City of Kediri, the contribution of MSMEs (Micro, Small and Medium Enterprises) includes the creative economy viewed from GDP (Gross Domestic Product) with the tobacco industry growing at 5.14 percent, without the tobacco industry at 7.02 percent. MSMEs also had a positive impact on reducing the number of open unemployed. In 2014, the unemployment rate in City of Kediri by 8 percent and now (2019) to 3.63 percent. The decline in the open unemployment rate also has an impact on reducing the poverty rate to 7.68 percent. The purpose of this study were to describe: 1) What was the contribution of the creative economy in the economic development of the City of Kediri (GDP - Gross Regional Domestic Product, economic growth, employment and poverty reduction)?, 2) What was the strategy for developing creative economy in the economic development of the City of Kediri?. Study showed: 1. Contribution of creative economy to the Gross Regional Domestic Product of Kediri City: a. Crafts or handicrafts (textile and apparel industry), b. Crafts (leather, leather goods, footwear), c. Crafts (furniture industry), d. Culinary (providing food and drink) e. Visual communication design; movies, animations, videos; publishing; music; Radio and Television f. Performing arts (entertainment and recreation and others), g. Kediri City Economic Growth. The value of Kediri's GRDP in 2019 based on 2010 was in constant prices, reached 90.01 trillion rupiah. This increase was up from 85.34 trillion rupiah in 2018. This showed that during 2019 there was economic growth of 5.47 percent, faster than the previous year's economic growth which reached 5.43 percent. h. employment during the last five years 2014-2019 (in 2019 there were 139,645 workers) the types of employment that employed the most labor were trade, restaurant and accommodation services, around 34.57-42.78 percent (meaning that culinary was included in the category of high labor absorption) and industrial jobs were around 11.59-17.78 percent (including the textile industry). i. Poverty. employment results in the amount of poverty in the city of Kediri experienced a decline where in 2016, it was 23,640 people, in 2017, there was a slight increase to 24,070 people and in 2018, it decreased to 21,900 people. In 2019, the number decreased again to 20,540 people. 2. Creative economic development strategies (plans and actions) are carried out by the quadruple helix (government, industry-private, universities and civil society-communities).